Case report: Severe acute hepatitis in a 22-month-old Chinese boy with Omicron sub-variant BA.2.38 - Chen, Xinying; Hong, Junbin; Li, Yuxia; An, Caixia; Guo, Jianwen; Yang, Jinghua (Frontiers in Public Health, 2022)
The etiology of severe acute hepatitis (SAH) in children is various. We describe the first Chinese case of severe acute hepatitis in a 22-month-old boy with the mild illness of Omicron sub-variant BA.2.38. With the application of Compound Glycyrrhizin Injection (CGI), the patient gradually recovered from acute liver injury (ALI). This case highlights the possibility of severe ALI in children with the non-critical illness of SARS-CoV-2. The management of SAH associated with the pandemic presents challenges for clinicians, and follow-up is in need. The method of differential diagnosis using limited laboratory results is of great value to the clinicians.